Project characteristics indicating safety performance - S. N. Yiu, Nicole; W. M. Chan, Daniel (International Journal of Engineering and Technology, 2018)
Safety performance has been long discussed and assessed in order to ensure less harm identified and reduce accidents in construction projects. Practically, accident rate is one common used key performance indicator to indicate the on-site safety performance in construction projects worldwide. Theoretically, there were various indicators that developed for the assessment of the safety performance of construction projects. These indicators were derived from previous literatures and lack of potential linkage to the project performance of construction projects. Thus, it is worth to explore the project characteristics that identified in construction projects with outstanding safety performance. This study introduced the project characteristics that identified in the construction projects with outstanding safety performance. The project characteristics were firstly identified by the sate-of-the-practice review and verified by panels of experts through structured interview and questionnaire survey. In general, findings of literature and structured interview were consistent. A series of interviews were supplemented the literaturesâ€™ findings. There were totally 27 project characteristics that indicating outstanding safety performance of a construction project. Eighteen experts were participated in the questionnaire surveys to verify the importance levels of the proposed project characteristics. All experts agreed with project characteristics that indicating the safety performance of the construction projects. The most agreed project characteristics were good housekeeping, more support and commitment from senior management, clear understanding of construction work activities, and good planning of project execution. These are indicative to future development of project management practice and sustainable safety strategies in construction industry locally and globally.Â